The roots of patriarchy - Ruggiu, Ilenia, author. Link
1 online resource
Keywords: "By combining legal and genealogical methodologies, this book describes the origin, decline, resurgence, and metamorphosis of patriarchy in the West. The book provides the reader with a unified tool to understand what patriarchy is, its dynamic and its main features. The reader will find a guide to navigate the dozens of definitions and theories of patriarchy, and will better understand why, despite the proclamation of formal Constitutions of the equality of the sexes, the gender gap in the West is still high. Approaching patriarchy both as a concept and as a social fact, the book shows how patriarchy lay at the Jewish-Greek-Roman roots of Western civilization; how for millennia it was perceived as a benevolent function for social and political life; and how feminism reversed this benevolent narrative. By reconstructing how patriarchy has been theorized in several disciplines and historical times, the book reflects on what has been done and remains to be done to de-patriarchalize the West. It will be a valuable resource for academics, researchers and students in Women's Studies, Gender Studies, Constitutional Law, Cultural Studies, Religious Studies and Anthropology"--